Firehouse dog - Steele, Michael Anthony; Lim, Claire-Dee.; Werb, Mike.; Colleary, Michael (New York : Scholastic, 2007)
Rex is the most famous and spoiled movie-star dog in the world. When he gets lost, he is taken in by a firehouse. He learns that being a "Firehouse Dog" can be just as exciting as and even more rewarding than being a Hollywood star.
CPL-MAIN CPL-ADDISN CPL-BRKLYN CPL-FLEET CPL-GLENV CPL-MTPLS CPL-SOUTH CPL-SOBRK CPL-STERL CPL-UNION CPL-WALZ CPL-WOOD MIL-MILAN KNSM-MAIN CPL-COLLWD
Keywords: Fire stations -- Juvenile fiction; Dogs -- Juvenile fiction; Heroes -- Juvenile fiction